Implementasi Manajemen Hubungan Sekolah dan Masyarakat Berbasis Kearifan Lokal - Reksa Adya Pribadi; Detin Isna Sofiatillah; Ulpah Ulpah; Yessi Hani Permatasari Pasaribu (Pendagogia: Jurnal Pendidikan Dasar, 2024)
School and community relationship management is a management of the relationship between the school and the community in order to create a good and harmonious relationship and the establishment of cooperation between the two parties. In this study, the implementation of school and community relationship management is reflected through a local wisdom-based activity program. The local wisdom-based activity is the commemoration of the Prophet's maulid or called Panjang Mulud. This study describes how the process of school and community relationship management based on local wisdom is precisely local wisdom in Banten Province at SDN Serang 21. By using qualitative research methods with descriptive qualitative approach type. The results obtained in this study are the existence of good relationship management between schools and local wisdom-based communities by adopting positive values in Pajang Mulud activities. So as to be able to provide good and positive learning for students and provide benefits to the surrounding community for the existence of these activities